A stimulatory GDP/GTP exchange protein for smg p21 is active on the post-translationally processed form of c-Ki-ras p21 and rhoA p21. - Mizuno, T (1991)
We have purified a stimulatory GDP/GTP exchange protein for smg p21A and -B, ras p21-like small GTP-binding proteins (G proteins), cloned its cDNA, and named it GDP dissociation stimulator (smg p21 GDS). We show here that smg p21 GDS is active not only on smg p21A and -B but also on c-Ki-ras p21 and rhoA p21, all of which are post-translationally processed. Furthermore, we show that smg p21 GDS is inactive on the post-translationally unprocessed form of these proteins and on the post-translationally unprocessed form of c-Ha-ras p21 and smg p25A. All of the small G proteins recognized by smg p21 GDS have a cDNA-predicted C-terminal "CAAX" motif (where C is cysteine, A is an aliphatic amino acid, and X is any amino acid) and a polybasic region upstream of this motif. These results suggest that smg p21 GDS is at least active on a group of small G proteins having these unique C-terminal structures. Moreover, they suggest that the C-terminal post-translational processing of these small G proteins, by farnesylation or geranylgeranylation of the C-terminal cysteine residue, removal of amino acids in positions denoted "AAX", and carboxyl methylation of the exposed cysteine residue, is important for the smg p21 GDS action.